2020
DOI: 10.2478/pcssr-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Factors directing individuals to computer games in the process of evaluating recreational activities

Abstract: AbstractThis study aims to examine the motivational factors that direct individuals to computer games in the process of evaluating leisure activities. The study is designed in descriptive and relational survey models, which are among the quantitative research patterns. A total of 1677 individuals participated in the study. A personal information form and the Computer Gaming Motivation Scale were used. An independent sample t-test, one-way analysis of variance, and Pearson corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…As for the other studies assessing gender related to motivations not related to the external and internal motivation framework of interpretation (other researchers used dimensions such as as competition and social), 6 studies found that, in general, males score higher than females in all or almost all game motivations [28,29,38,47,50,54], even though Demetrovics et al [22] found contradicting results showing that women tend to score higher on recreation, social, coping, fantasy, skill development, and escape except competition. In fact, 5 studies confirmed that female players tend to score higher than males on the relationship motivation [22,[25][26][27]67], 3 studies found that females score higher on social motivation [22,29,47], 3 studies found that females score higher on escapism [22,25,67], and 2 on fantasy [22,67].…”
Section: Results Related To the Sociodemographic Variablesmentioning
confidence: 96%
See 4 more Smart Citations
“…As for the other studies assessing gender related to motivations not related to the external and internal motivation framework of interpretation (other researchers used dimensions such as as competition and social), 6 studies found that, in general, males score higher than females in all or almost all game motivations [28,29,38,47,50,54], even though Demetrovics et al [22] found contradicting results showing that women tend to score higher on recreation, social, coping, fantasy, skill development, and escape except competition. In fact, 5 studies confirmed that female players tend to score higher than males on the relationship motivation [22,[25][26][27]67], 3 studies found that females score higher on social motivation [22,29,47], 3 studies found that females score higher on escapism [22,25,67], and 2 on fantasy [22,67].…”
Section: Results Related To the Sociodemographic Variablesmentioning
confidence: 96%
“…Other four questionnaires that were fairly used in the analyzed papers were as follows: (a) The Player Experience of Need Satisfaction (PENS, [30]) (n = 5), which based on the Self-Determination Theory [31], assesses five main dimensions: presence 54 , competence 12 , relatedness 58 , autonomy 7 , and intuitive controls 41 ; (b) the Motive for Online Gaming Questionnaire (MOGQ; [22]) (n = 5) which assesses seven main motivations: competition 13 , coping 15 , fantasy 28 , social 65 , skill development 63 , escape 25 , and recreation 57 ; (c) the Gaming Motivation Scale (GAMS; [32]) (n = 5) which assesses five dimensions: intrinsic motivation 38 , integrated regulation 36 , identified regulation 34 , introjected regulation 40 , external regulation 27 , and amotivation 5 ; (d) the Online Gaming Motivations Scale [27] (n = 5) which assesses three main motivations: immersion 35 , achievement 1 , and social 65 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations